10-year nationwide trends in incidence, treatment patterns, and mortality of patients with myelodysplastic syndromes in Denmark. (May 2023) - Lauritsen, Tine Bichel; Nørgaard, Jan Maxwell; Dalton, Susanne Oksbjerg; Grønbæk, Kirsten; El-Galaly, Tarec Christoffer; Østgård, Lene Sofie Granfeldt
Abstract: Further temporal data on incidence, treatment patterns, and prognosis for patients with myelodysplastic syndromes (MDS) are needed. This study examined 10-year trends in incidence, treatment patterns, and all-cause mortality in a population-based cohort of 2309 MDS patients using Danish nationwide registries (2010–2019). We computed annual incidence rates overall and according to sex and age-groups. We examined temporal changes in the cumulative incidence of MDS specific treatments initiated within one year from diagnosis and temporal changes in the absolute risk of death and five-year adjusted hazard ratios (aHRs) for death, adjusting for age, sex and comorbidity. The age-standardized incidence rate of MDS per 100, 000 person-years increased slightly from 5.3 in 2010 to 6.4 in 2019. Between 2010-2012 to 2016–2017, the use of azacitidine increased overall (8% to 22%), in patients with intermediate risk MDS (12% to 34%), and in patients with high-risk MDS (22% to 50%), while it remained stable (around 5%) for patients with low-risk MDS. The five-year aHR for death in the most recent calendar period compared to the earliest calendar period remained unchanged in patients with low-risk MDS, aHR = 0.90 (95% CI, 0.72–1.12) and in patients with high-risk MDS, aHR = 1.19 (95% CI, 0.89–1.61), while survival improved over time among patients with intermediate risk MDS, aHR = 0.67 (95% CI, 0.48–0.92). In conclusion the incidence of MDS slightly increased during a 10-year period in Denmark. The use of azacitidine increased markedly but five-year overall survival remained unchanged. Highlights: The incidence of MDS increased in individuals aged 80 years or older (2010–2019). The use of erythropoiesis-stimulating agents decreased (2010–2018). The use of azacitidine increased (2010–2018). Survival was unchanged in patients with low-risk and high-risk MDS (2010–2021). Survival improved in patients with intermediate-risk MDS (2010–2021).